Pengaruh Perceived Risk dan Credibility Terhadap Purchase Intention Jasa War Tiket Konser Melalui Trust di Indonesia(Studi Empiris Konser K-Pop) - Andari Prayudi, Zahra Aisyah; Munawaroh, Munawaroh; Fadlullah, Fauzan (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to examine the influence of perceived risk and credibility on purchase intention toward concert ticket “war” services, with trust serving as a mediating variable. This research employs a quantitative approach, with data collected through an online questionnaire distributed via Google Form to members of the “SEVENTEEN NEW_ IN JAKARTA SOON” community on the X (Twitter) platform. The community is known for actively sharing concert information, ticketing strategies, and peer-to-peer ticket transactions, making it relevant for representing consumer behavior toward concert ticket third-party services. The sample was determined using a purposive sampling technique based on specific criteria, involving 105 respondents with a total of 13 indicators covering 4 perceived risk indicators, 4 credibility indicators, 5 trust indicators, and 4 purchase intention indicators. The research instrument used a 5-point Likert scale to measure respondents’ perceptions of each variable indicator. Data were analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method, with mediation testing conducted through bootstrapping techniques. The results indicate that credibility has a positive and significant effect on trust and purchase intention, and trust also has a positive and significant effect on purchase intention. Furthermore, trust partially mediates the relationship between credibility and purchase intention. In contrast, perceived risk does not have a significant effect on trust or purchase intention, nor does it have an indirect effect on purchase intention through trust. These findings suggest that in the context of K-Pop concert ticket “war” services in Indonesia, credibility and trust play a more dominant role in shaping purchase intention than perceived risk.